INVESTIGAÇÃO MATEMÁTICA: UMA PROPOSTA DE ENSINO DE ESTATÍSTICA PARA O 8° ANO DO ENSINO FUNDAMENTAL - Guerra, Sheila Heydt Réquia (2015)
This study aimed to analyze if the methodology of mathematics research contributes to teaching basic concepts of Statistics in a class of 8th grade of elementary school. The participants were 24 students from a public school in the city of Santa Maria, Rio Grande do Sul state. This research was developed from the professional motivation in proposing research activities involving the concepts of Statistics. The methodology of work was based from the qualitative research, where the researcher was directly involved in all stages of the research and data collection instruments used were participant observation, the field diary for recording events during application of units proposed and the analysis of documents produced by the students. Also, in video and audio recordings were made to make it true and accurate understanding and analysis of the dialogues during the course of the investigation. During the investigation it was applied a didactic sequence subdivided into two teaching units whose purpose was to analyze the process followed by students in the construction of the basic concepts of Statistics, using the methodology of mathematical research. As a result of analysis, it could show that the vast majority of students took an active role during the stages of research, promoting the development of skills that include communication, decision making, teamwork, discussion and argumentation, beyond the mathematical calculation. Another aspect to be highlighted was the great involvement and enthusiasm of the students in this type of work, even having contact with the first methodology in schools. In this sense, the results obtained showed that, after application of the didactic sequence, the methodology of mathematical research, supported the Information and Communication Technologies, contributed effectively to the learning of statistical concepts and enabled greater involvement of the same in mathematics classes.